Estudo dos pontos anatômicos de referência para osteotomia sagital do ramo mandibular com tomografia computadorizada de feixe cônico e software Dolphin* - Casagrande, Liliane Cristina Onofre (2017)
The sagittal split ramus osteotomy is widely used for the surgical correction of den-tofacial deformities. The techniques historical development began with Hugo Obwer-geser in 1957. The relentless proposals for alterations of the sagittal split ramus oste-otomy technique originated with the intention of administering and minimizing the var-ious trans and pos-operative complications that happened during the performance of this procedure. As this is a technique usually employed with young healthy patients, the rates of complications must be controlled and the possible factors of confusion must be detected and corrected. The present study had the purpose of identifying mandibular anatomical points, using cone beam computed tomography, and ana-lise their relation with areas and structures that are important for surgical planing, in the exams of patients with retrognathism, prognathism and with a balanced maxillo-mandibular pattern using Dolphin® software. 27 tomographic patient images were dis-tributed into the three groups and were evaluated. Significant statisti-cal diferences were found between the three evaluated deformities and between men and women. However, the mandibular canal had a greater distance to the vestibular cortical plate in the points between the distal root of the first molar and de distal root of the second molar, and was closer to the lingual plate in the region between 1M and 2M, in all three classes.